A Simple Model Setup Using Spray‐Drying Principles and Fluorescent Silica Nanoparticles to Evaluate the Efficiency of Facemask Materials in Terms of Virus Particle Retention. Issue 6 (4th May 2021) - Oppmann, Maximilian; Wenderoth, Sarah; Ballweg, Thomas; Schug, Benedikt; Mandel, Karl
Abstract: Herein, a simple model setup is presented to spray fine liquid droplets containing nanoparticles in an air stream transporting this toward a filter material. The nanoparticles are made of silica and tagged with a fluorescent dye in order to render the trace of the particles easily visible. The silica nanoparticles, in a first approximation, mimic virus (severe acute respiratory syndrome coronavirus 2) particles. The setup is used to evaluate different tissues, nowadays, in times of the coronavirus pandemic, commonly used as facemasks, with regard to their particle retention capability. The setup enables adjusting different "breathing scenarios" by adjusting the gas flow speed and, thereby, to compare the filter performance for these scenarios. The effective penetration of particles can be monitored via fluorescence intensity measurements and is visualized via scanning electron micrographs and photographs under UV light. Ultimately, a strong increase of particle penetration in various mask materials as function of flow speed of the droplets is observed and an ultimate retention is only observed for FFP3 and FFP2 masks. Abstract : Herein, an approach to easily test the retention capability of different mask materials toward aerosol droplets, filled with nanoparticles, mimicking virus particles, is presented. This is done using a modified spray‐drying setup that can create a stream of aerosol droplets filled with fluorescent silica nanoparticles hitting toward a target tissue. Penetrated fluorescent particles are collected and visualized downstream.